2018
DOI: 10.1038/s41418-018-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

M1-linked ubiquitination by LUBEL is required for inflammatory responses to oral infection in Drosophila

Abstract: Post-translational modifications such as ubiquitination play a key role in regulation of inflammatory nuclear factor-κB (NF-κB) signalling. The Drosophila IκB kinase γ (IKKγ) Kenny is a central regulator of the Drosophila Imd pathway responsible for activation of the NF-κB Relish. We found the Drosophila E3 ligase and HOIL-1L interacting protein (HOIP) orthologue linear ubiquitin E3 ligase (LUBEL) to catalyse formation of M1-linked linear ubiquitin (M1-Ub) chains in flies in a signal-dependent manner upon bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 67 publications
0
44
0
Order By: Relevance
“…Additional regulation may explain the residual signaling within the I. scapularis IMD network. For example, the Drosophila HOIL-1L interacting protein (HOIP) ortholog linear ubiquitin E3 ligase (LUBEL) works in concert with dIAP2 to activate Relish through methionine 1dependent ubiquitylation of Kenny (66). This is expected, as the transduction of NF-κB is tightly modulated through redundancy to prevent aberrant inflammation and limit fitness costs (7,58).…”
Section: Discussionmentioning
confidence: 99%
“…Additional regulation may explain the residual signaling within the I. scapularis IMD network. For example, the Drosophila HOIL-1L interacting protein (HOIP) ortholog linear ubiquitin E3 ligase (LUBEL) works in concert with dIAP2 to activate Relish through methionine 1dependent ubiquitylation of Kenny (66). This is expected, as the transduction of NF-κB is tightly modulated through redundancy to prevent aberrant inflammation and limit fitness costs (7,58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the microvascular damage caused by endothelial cell apoptosis and capillary obstruction significantly reduces the effectiveness of reperfusion therapy and may compromise the clinical benefits in patients with AMI (Chrifi et al 2019). Therefore, microvascular damage is upstream of cardiomyocyte damage (Aalto et al 2019). At last, given the direct contact between the Jiankai Zhong and Haichun Ouyang contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate how drICE-mediated cleavage of DIAP2 regulates IMD signalling, we examined the ability of DIAP2 to ubiquitinate its substrates in the presence or absence of active drICE. DIAP2-mediated K63linked ubiquitination of the IMD pathway components IMD and DREDD has been shown to be required for IMD signalling, and the Drosophila NEMO, IKKγ or Kenny, has recently been identified as a target of K63-linked ubiquitination mediated by DIAP2 (Paquette et al, 2010, Meinander et al, 2012, Aalto et al, 2019. While drICE activity was induced by overexpressing drICE in S2 cells, drICE was inhibited by overexpression of the catalytically inactive drICEC211A or by treatment with synthetic caspase-3 inhibitor Z-DEVD-FMK.…”
Section: Drice Interferes With the With The E3 Ligase Activity Of Diap2mentioning
confidence: 99%
“…Activation of PGRP-LCx leads to the recruitment of the adaptor proteins IMD and dFADD, and the initiator caspase DREDD (Choe et al, 2005). DREDD-mediated cleavage of IMD exposes a conserved IAP-binding motif that recruits DIAP2 to the complex, stimulating DIAP2-mediated K63-ubiquitination of IMD, DREDD and the IKK Kenny (Paquette et al, 2010, Meinander et al, 2012, Aalto et al, 2019. Ubiquitination of DREDD is needed for cleavage and nuclear localization of the NF-κB protein Relish (Stoven et al, 2003, Meinander et al, 2012, whereas ubiquitination of IMD has been suggested to recruit the Drosophila mitogen-activated protein kinase kinase kinase dTAK1 and the Relish kinase complex IRD5/Kenny to the IMD signalling complex (Ferrandon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%